Use of the Robson classification to understand the increased risk of cesarean section in case of maternal obesity - Simon Crequit; Diane Korb; Cécile Morin; Thomas Schmitz; Olivier Sibony (BMC, 2020)
Abstract Background The aim of this study was to identify characteristics of pregnant women with obesity that contribute to increased cesarean rate. Methods Retrospective cohort in a single academic institution between 2012 and 2019. Women who delivered during this period were classified according to the Robson classification. Women with normal body mass index (N = 11,797) and with obesity (N = 2991) were compared. The contribution of each Robson group to the overall caesarean rate were compared. Results The overall cesarean rate was higher for women with (28.1%) than without (14.2%, p < 0.001) obesity. This result came mainly from Robson group 5a (history of one cesarean). After adjustment for medical factors within this group, the association between maternal obesity and cesarean during labor was significant. Conclusions The higher cesarean rate in women with obesity is explained by Robson group 5a in which obesity is an independent risk factor of in labor cesarean delivery.